Evaluation of right ventricular function performed by 3d-echocardiography in scleroderma patients - E. Pigatto; D. Peluso; E. Zanatta; P. Polito; P. Miatton; K. Bourji; L. P. Badano; L. Punzi; F. Cozzi (PAGEPress Publications, 2015)
The impairment of the right ventricle (RV) in systemic sclerosis (SSc) is usually related to pulmonary arterial hypertension (PAH). New echocardiographic techniques, such as 3-dimensional echocardiography (3DE) and 2-dimensional speckle tracking (2DSTE), allow an accurate evaluation of the RV function. The aim of this study was to evaluate the RV function using 3DE and 2DSTE in SSc patients with no history of heart disease and no PAH. Forty-five SSc patients, 42 females and 3 males, 28 with limited cutaneous SSc (lcSSc) and 17 with diffuse cutaneous SSc (dcSSc), were studied. Forty-three age- and gender-matched healthy subjects were enrolled as controls. All of them underwent a 3DE and 2DSTE ecocardiographic evaluation of the RV function. Systolic pulmonary arterial pressure (sPAP) and total pulmonary vascular resistance (tPVR) were also estimated by power doppler. RV echocardiographic parameters were compared in the different subsets of SSc patients. A statistical analysis was performed by t-test, ANOVA and multiple logistic regression. RV areas in 2DSTE and volumes in 3DE were higher and RV function parameters were reduced in SSc patients compared with controls. Also sPAP and tVPR were higher, but they did not reach pathological values. Echocardiographic alterations were more pronounced in patients with lcSSc. 3DE and 2DSTE echocardiography allowed us to detect morphological and functional alterations of the RV in a group of SSc patients with no clinical signs of heart disease and no PAH. These patients had significantly higher sPAP and tPVR than healthy controls without reporting values compatible with PAH. These data suggest that RV alterations are related to a pressure overload rather than to an intrinsic myocardial involvement in SSc.